2022
DOI: 10.3389/fphar.2022.875611
|View full text |Cite
|
Sign up to set email alerts
|

Gut Metabolite Urolithin A Inhibits Osteoclastogenesis and Senile Osteoporosis by Enhancing the Autophagy Capacity of Bone Marrow Macrophages

Abstract: Senile osteoporosis (SOP) is a systemic bone disease that is significantly associated with age and eventually leads to deteriorated bone strength and increased fracture risk. Urolithin A (Uro-A) is a gut microbiome-derived compound that is mainly produced from pomegranates and some nuts. Uro-A has attracted great attention in recent years in view of its protective effects on aging-related diseases, including muscle dysfunction, kidney disease and knee injury. However, its protective influence and possible mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The trial duration was too short to assess BMD changes. However, several preclinical studies have demonstrated an inhibition of osteoclastogenesis and a decrease in experimental bone loss, raising some hope on the effect of urolithin A on bone health [ 49 , 50 ].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…The trial duration was too short to assess BMD changes. However, several preclinical studies have demonstrated an inhibition of osteoclastogenesis and a decrease in experimental bone loss, raising some hope on the effect of urolithin A on bone health [ 49 , 50 ].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…The final three musculoskeletal-related studies focus on age-related bone and joint pathology [ 21 , 22 ]. UA supplementation has also shown promise as an anti-aging remedy in the development of osteoporosis [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…The final three musculoskeletal-related studies focus on age-related bone and joint pathology [ 21 , 22 ]. UA supplementation has also shown promise as an anti-aging remedy in the development of osteoporosis [ 21 ]. In a 2022 study completed by Tao et al, a significant reduction in bone resorption and osteoclast-related gene expression was seen in human cell samples treated with 5 and 10 μM doses of UA [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations